PENGARUH KEBERHASILAN DIRI, TOLERANSI AKAN RISIKO, DAN KEBEBASAN DALAM BEKERJA TERHADAP MOTIVASI BERWIRAUSAHA PADA MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI STKIP PGRI BANGKALAN - Sari, Indah Purnama (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2013)
The aim of this research was to investigate the influence of self achievement, risk of tolerance, and freedom of work on enterpreneurships motivation. The population as same as the sample were 120 of seventh semester student at the economic education program of STIKIP PGRI Bangkalan in the academic year 2012/2013. The data were collected through questionaires.The data were then analyzed with quantitative analysis by multiple linier regressions. Based on the partial test (t test), it showed that self achievement had significant influence on enterpreneurships motivation, risk of tolerance had significant influence on enterpreneurships motivation while freedom of work had not significant influence on enterpreneurships motivation. Based on the significance test (f test), it showed simultaneously that self achievement, risk of tolerance and freedom of work had significant influence on enterpreneurships motivation.